(untitled) (Global Journal of Science Frontier Research, 2022)
Aim Synthetic insecticides are widely being used for the control of mosquitoes However this is faced with many challenges among which are development of insecticide resistance by the mosquitoes damage to the environment effect on human health and non-target organisms This study thus aimed at comparing the larvicidal effect of leaves extracts of Cymbopogoncitratus Lemon grass and Xymenia-americana Sea lemon against anopheles and culex larvae Method The leaves components were extracted and phytochemical analyses of the extracts were also done Anopheles and culex larva were collected and identified using morphological features Larvicidal susceptibility test were carried out using WHO standard method and the mortalities were observed after 24 hours and 48 hours of exposure Results Higher mortality was observed in anopheles larvae exposed to ethanol leaf extracts of C citrates after 24 hours of exposure LC50 5 905mg ml and LC90 16 241mg ml compared to the ethanol leaf extract of X americana with the lower motality after 24 hours of exposure LC50 7 617mg ml and LC90 43 471mg ml Against culex larvae higher motality was also observed in ethanol leaf extract of C citrates after 24 hours of exposure LC50 6 851mg ml and LC90 25 678mg ml compared to ethanol leaf extract X americana with the lower motality after 24 hours of exposure LC50 10 626mg ml and LC90 54 434mg ml Conclusion The result suggest that the ethanol leaf extract of the plants used possessed significant larvicidal activities against the anopheles and culex laeva However the C citratus extract is more potent than that of the X Americana extract These show that they may be considered as natural sources for the production of natural larvicides